Religious Discrimination In My Name Is Khan Movie - Putri Annisa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In recent times, literature has become a popular subject among the people. Because there is a lot of beauty in it, and also never far from the relationship between society and individuals and between individuals and events. Literature produces many works called literary works. Literary works are not only in the form of novels and poetry but can also be in the form of movies. The author chose this data source so that people can be more aware of concerns. There are two objectives in this study, the first is to find out what types of worries are contained in My Name is Khan movie, and the second is to analyze how the main character in My Name is Khan movie struggles against the stigmatization of Islam as a terrorist religion. This study uses a qualitative descriptive method, a qualitative descriptive approach is a research approach where the data collected is in the form of words, pictures, and not numbers. Because it occurs naturally, the research results are of course also scientific and measurable. In this method, the researcher tries to describe the facts obtained to provide clues about the problem being studie d.This movie shows us the reality that there are still many people in this world who have thoughts like this. Superficial and judging someone only based on their identity without wanting to know what it is. This still often happens in our lives, people who are discriminated against just because of their religion are considered to be wrong. The types of religious discrimination in the movie My Name is Khan that are visible and proven in the previous chapter are Harassment by insulting Islam directly and Bullying with physical violence experienced by the characters in My Name Khan movie. Harassment experienced by the characters in My Name is Khan's movie. Words in the form of swear words. Swearing in the case of this research is used by a person or group to express all forms of dissatisfaction and anger toward the situation they are facing. After analyzing the data in the previous chapter, it can be concluded that Khan’s struggle against the stigmatization of Islam was by meeting the President of the United States, Barack Obama. To tell and prove to the whole world that he and his religion are not terrorists. This was also proven in his dialogue with Dr. Faisal Rahman who created a bad image of Islam and taught acts of revenge. Even though the fact is that Islam has never been taught that way.